Analisis Sikap Masyarakat terhadap Lesbian, Gay, Biseks, Transgender (LGBT) di Kota X Sumatera Barat - Novia Zulfa Hanum; Tosi Rahmaddian; Fitria Fitria (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
LGBT stands for Lesbian, Gay, Bisexual and Transgender. LGBT is a form of sex deviation more than adultery and ambulance. This research is a cross-sectional study with an analytical approach. population is carried out purposively, with a sample amount of 104 people. Results from 104 respondents, 63 respondents (60,6%) with negative categories, and 41 respondents (39,4%) with positive categories. The result shows the difference in positive attitudes (pro) and negative (contra) of the X city in West Sumatera, the existence of LGBT is not significant. The negative attitude on the religious basis looks at statements “The LGBT Employment is contrary to the religious teachings and great sins” with the respondent score respondent strongly agreed as 56.7% and agreed as much as 32.7% and “I will cover the LGBT friends to repent” with the respondent score respondent strongly agreed as 49% and agreed as 45.2%. Apart from religious reasons, the negative attitude of respondents towards LGBT was also shown in the statement